Implementation of endoscopic submucosal dissection for early upper gastrointestinal tract cancer after primary experience in colorectal endoscopic submucosal dissection - Mocker, Lena; Hildenbrand, Ralf; Oyama, Tsuneo; Sido, Bernd; Yahagi, Naohisa; Dumoulin, Franz Ludwig (Endoscopy International Open, 2019)
Background Current guidelines recommend endoscopic submucosal dissection (ESD) as a treatment option for early cancers of the upper gastrointestinal tract with absent or minimal risk of lymph node metastasis. However, due to the low prevalence of these entities, it is difficult to achieve a competence level for ESD of upper gastrointestinal tract cancers in the Western World. Here, we present single-center data on the implementation of upper gastrointestinal ESD after previous experience with 89 colorectal ESD cases.Methods Retrospective case series of 39 consecutive patients with early cancers of the esophagus (n = 13) or cardia and stomach (n = 26) treated with ESD over a 4-year period.Results ESD was technically feasible in all cases with en bloc, R0, and curative resection rates of 100 %, 76.9 %, and 71.8 %, respectively, and a mean procedure time of 100 minutes (30 – 360 minutes). After an initial 20 procedures, the R0 and curative resection rates increased from 65.0 % to 89.5 %, and from 60.0 % to 84.2 %, respectively. Complications were observed in four patients (10.3 %): three perforations, one case of delayed bleeding, and one esophageal stricture. No case required emergency surgery; the 30-day mortality rate was 0 %.Conclusion In this modest case series from Europe, we observed an effectiveness and complication rate for ESD for early esophageal and gastric cancer that are comparable to other series from Europe but also to more abundant data from Asia. The results indicate that even small numbers of upper gastrointestinal cancers can be managed adequately in centers with expertise in colorectal ESD.